A Combination therapy using an mTOR inhibitor and Honokiol effectively induces autophagy through the modulation of AXL and Rubicon in renal cancer cells and restricts renal tumor growth following organ transplantation. (29th December 2021) - Sabarwal, Akash; Wedel, Johannes; Liu, Kaifeng; Zurakowski, David; Chakraborty, Samik; Flynn, Evelyn; Briscoe, David M; Balan, Murugabaskar; Pal, Soumitro
Abstract: Development of cancer, including renal cancer, is a major problem in immunosuppressed patients. The mTOR inhibitor Rapamycin (RAPA) is used as an immunosuppressive agent in patients with organ transplants and other immunological disorders; and it also has antitumorigenic potential. However, long-term use of RAPA causes reactivation of Akt, and ultimately leads to enhanced tumor growth. Honokiol (HNK) is a natural compound, which possesses both anti-inflammatory and antitumorigenic properties. In this study, we investigated the effect of a novel combination therapy using RAPA + HNK on allograft survival and post-transplantation renal tumor growth. We observed that it effectively modulated the expression of some key regulatory molecules (like Carabin, an endogenous Ras inhibitor; and Rubicon, a negative regulator of autophagy) that play important roles in tumor cell growth and survival. This combination induced toxic autophagy and apoptosis to promote cancer cell death; and was associated with a reduced expression of the tumor-promoting receptor tyrosine kinase AXL. Finally, we utilized a novel murine model to examine the effect of RAPA + HNK on post-transplantation renal tumor growth. The combination treatment prolonged the allograft survival and significantly inhibited post-transplantation tumor growth. It was associated with reduced tumor expression of Rubicon and the cytoprotective/antioxidant heme oxygenase-1 to overcome therapeutic resistance. It also downregulated the coinhibitory programmed death-1 ligand, which plays major role(s) in the immune escape of tumor cells. Together, this combination treatment has a great potential to restrict renal tumor growth in transplant recipients as well as other immunosuppressed patients. Abstract : The schematic diagram showing how RAPA + Honokiol combination can prevent post-transplantation cancer through autophagy- and apoptosis-mediated cancer cell death, and inhibition of immune cell escape. Graphical Abstract: